Male Humpback Whale Chorusing in Hawai‘i and Its Relationship With Whale Abundance and Density - Kügler, Anke; Lammers, Marc O.; Zang, Eden J.; Pack, Adam A. (Frontiers in Marine Science, 2021)
Passive acoustic monitoring (PAM) with autonomous bottom-moored recorders is widely used to study cetacean occurrence, distribution and behaviors, as it is less affected by factors that limit other observation methods (e.g., vessel, land and aerial-based surveys) such as inclement weather, sighting conditions, or remoteness of study sites. During the winter months in Hawai‘i, humpback whale male song chorusing becomes the predominant contributor to the local soundscape and previous studies showed a strong seasonal pattern, suggesting a correlation with relative whale abundance. However, the relationship between chorusing levels and abundance, including non-singing whales, is still poorly understood. To investigate how accurately acoustic monitoring of singing humpback whales tracks their abundance, and therefore is a viable tool for studying whale ecology and population trends, we collected long-term PAM data from three bottom-moored Ecological Acoustic Recorders off west Maui, Hawaii during the winter and spring months of 2016–2021. We calculated daily medians of root-mean-square sound pressure levels (RMS SPL) of the low frequency acoustic energy (0–1.5 kHz) as a measure of cumulative chorusing intensity. In addition, between December and April we conducted a total of 26 vessel-based line-transect surveys during the 2018/19 through 2020/21 seasons and weekly visual surveys (n = 74) from a land-based station between 2016 and 2020, in which the location of sighted whale pods was determined with a theodolite. Combining the visual and acoustic data, we found a strong positive second-order polynomial correlation between SPLs and abundance (land: 0.72 ≤ R2 ≤ 0.75, vessel: 0.81 ≤ R2 ≤ 0.85 for three different PAM locations; Generalized Linear Model: pland ≪ 0.001, pvessel ≪ 0.001) that was independent from recording location (pland = 0.23, pvessel = 0.9880). Our findings demonstrate that PAM is a relatively low-cost, robust complement and alternative for studying and monitoring humpback whales in their breeding grounds that is able to capture small-scale fluctuations during the season and can inform managers about population trends in a timely manner. It also has the potential to be adapted for use in other regions that have previously presented challenges due to their remoteness or other limitations for conducting traditional surveys.